ВПЛИВ ДЖЕРЕЛА ЗБУДЖЕННЯ НА СИЛОВІ ПОКАЗНИКИ ЛІНІЙНОГО ІМПУЛЬСНОГО ЕЛЕКТРОМЕХАНІЧНОГО ПЕРЕТВОРЮВАЧА ІНДУКЦІЙНОГО ТИПУ - Болюх, В.Ф.; Щукін, І.С. (Інститут електродинаміки НАН України, Київ, 2021)
The purpose of the article is to evaluate the efficiency of an induction-type linear pulse electromechanical converter (LPEC) when operating in shock-power mode and excitation from an alternating voltage source (AVS) in comparison with excitation from a capacitive energy storage (CES). A mathematical model of an induction-type LPEC has been developed both when excited by a unipolar pulse from a CES and from an AVS using lumped parameters of the windings, which takes into account the interrelated electromagnetic, mechanical and thermal processes. It has been found that when the LPEC is excited from the AVS with a voltage frequency of 50 Hz, the electrodynamic force takes on a periodic decaying character with a significant prevalence of positive components of forces over negative ones. The maximum value of the force is much less, and the value of its impulse is much greater than in the LPEC, excited from the CES. With an increase in the frequency of the AVS voltage from 50 to 150 Hz, the highest value of the current density of the inductor winding decreases, and in the armature winding it increases. The greatest values of force and impulse of force are realized at a voltage frequency of 150 Hz. With an increase in the AVS frequency, the relative indicator of the efficiency of the LPEC increases. References 15, figures 4.